THE EFFECT OF NUMBERED HEAD TOGETHER ON ENGLISH WRITING DESCRIPTIVE PARAGRAPH - Evi Kasyulita (JEE (Journal of English Education), 2015)
This study explains and concludes that the existence of teaching writing for junior high school students using Numbered Head Together (NHT). According to some experts, learning in groups (Numbered Head Together) also offers a different outcome judging from the initial abilities possessed by students. The purpose of this study was to determine the effect of the Numbered Head Together strategy and the ability to write English. This study used an experimental method conducted at SMP Nurul Falah Pekanbaru, Riau with a sample of 60 students in the second grade students of SMP Nurul Falah Pekanbaru. The results of this study are; (There is a significant effect of the use of the Numbered Head Together strategy of students on the ability to write English students in the second grade students of SMP Nurul Falah Pekanbaru Riau. Which is proven that if, t is a large observation of t table then there is an effect of the strategy. For the results obtained values ​​from t observation is 7.31 and t table is 2,000, it can be concluded that if (7.13> 2.000) then there is an effect of using Numbered Head Together strategy on the ability to write English in grade 2 students of SMP Nurul Falah Pekanbaru.